(3ePcQGJ CHj eYTQ aj CSQGQ Yde GdfLhes - (3LYaQ Hf eMeO Hf YeQ GdHdNj, CHh eYTQ , nCoHh nerYnTQ Gdnandcj,J (B272 (3g` s
(3ChdgG (B:s
(3CeG HYO agPg ePcQGJ CHh eYTQ ai CSQGQ Yde GdfLhe hSDGd CHj SYjO TGOGf s
(3BNQgG (B:s
(3hUGMH GdfXjQ jJUd Hg aEfg jOd Ydi GdXaQ HEPf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdChdis
(3HgG fXGe GdJYbjHIs
(3gPg ePGcQGJ CHheYTQ ai CSQGQ Yde GdfLhe hSDGd CHj SYjO TGPGf Hf HMQ Yf CHj eYTQ hLhGHGJ CH eYTQ dgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B148s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1643s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs